Klasifikasi Penyakit HepatitisC Menggunakan Algoritma Support Vector Machine - Ni Kadek Trisnawati; I Gede Santi Astawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
Hepatitis is an inflammation of the liver which is often caused by a virus. Hepatitis that lasts less than 6 months is called "acute hepatitis", hepatitis that lasts more than 6 months is called "chronic hepatitis" Hepatitis consists of various types starting from hepatitis A, B, C, D and E. This study will discuss the classification Hepatitis C is classified as blood based (blood donor), suspected blood donor, fibrosis (moderate to severe hepatitis) and cirrhosis (chronic hepatitis). Classification uses the Support Vector Machines (SVM) algorithm with Confusional Matrix testing. The dataset used was obtained from the kaggle.com site with a total of 590 data consisting of 14 features or attributes. This study produces an accuracy of 93%